X-ray spectral analysis of surface structures formed on copper alloys during film fasting - Kubich, V.I.; Cherneta, O.G.; Yurov, V.M.; Oleshko, V.S. (Journal of Physics: Conference Series, 2021)
The paper establishes the nature of the redistribution of chemical elements and their concentration in secondary surface structures for the material systems "steel 45XN2MFAgrease- BrOTsS4-4-2.5", "steel 45XN2MFA-grease-BrOTsS4-4-4", "steel 45XN2MFA-grease - L-63 ", tested under the conditions of simulating film starvation when lubricated with 15W40 Lukoil-Super SAE SG/CD engine oil. Since the formula obtained by us includes the Gibbs energy, the self-organization of the structure under consideration naturally also enters. General laws of self-organization are observed when a number of conditions are met: irreversibility, openness (nonequilibrium), nonlinearity, instability (coherence), dissipativity. All these elements were observed and described by us in this work. It is due to self-organization that the distribution of chemical elements carbon and oxygen occurred on the surfaces L63 and BrOF4- 4-4. To this effect must be added a decrease in the surface tension of the lubricant.
Keywords: tribosystem of materials; chemical element; copper alloy; surface; scanning area; analysis